HCP5 Derived Novel Microprotein Triggers Progression of Gastric Cancer through Regulating Ferroptosis - Qiuhui Li; Guoqing Guo; Yuli Chen; Lu Lu; Hanyang Li; Zihan Zhou; Jiahao Guo; Xiongkang Gan; Yanming Hu; Qiunuo Li; Ming Sun; Xianghua Liu (Advanced Science)
Abstract The context of long noncoding RNAs (lncRNAs) contains many unannotated open reading frames (ORFs). These ORFs potentially encode novel proteins or peptides with crucial roles in various human cancers, yet the translational potential of these lncRNAs and the functions of the protein products remain largely unexplored, especially in gastric cancer (GC). In this study, a comprehensive analysis is performed and identified a GC associated lncRNA known as HCP5, which contains a non‐canonical ORF. Further analysis showed that HCP5‐132aa, a microprotein encoded by HCP5 harboring this ORF, is highly expressed in GC cells and tissues, and can promote the proliferation of GC cells by inhibiting ferroptosis. Mechanistically, HCP5‐132aa enhances the interaction between YBX1 and ELAVL1, facilitates recognition of YBX1 at the m5C site in the 3′UTR of SLC7A11 and G6PD mRNA, and preserves their stability via ELAVL1. By employing a Cas9/sgRNA delivery system with AAV in vivo, effectively knocked out the HCP5‐132aa and inhibition of tumor growth in a patient‐derived xenograft model are achieved. These findings demonstrate that the novel protein HCP5‐132aa, derived from lncRNA HCP5, mediates the repression of ferroptosis, thereby driving the progression of GC and identifying a new potential therapeutic target for its treatment.